Implementations of Code Switching in The Characters of The Movie “Everything Everywhere All At Once” - Athaillah, Siti Adhwa; Ma'wa, Kesya Asyura; Rosalinah, Yanti (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study examines the use of code-switching among characters in the movie Everything Everywhere All at Once (2022), which portrays the bilingual Mandarin–English experiences of Chinese-American immigrants living within a multicultural environment. Employing a qualitative descriptive method, the research focuses on analyzing naturally occurring language patterns in the film. Data were collected through systematic observation and transcription of the movie’s dialogues, followed by detailed identification of utterances containing language alternation. The analysis was conducted using Poplack’s (1980) framework, which categorizes code-switching into intra-sentential, inter-sentential, and tag switching. The results reveal that intra-sentential switching is the most dominant type, accounting for 64% of the total instances. This type appears frequently in emotionally expressive conversations, demonstrating the characters’ high bilingual proficiency and their tendency to blend linguistic resources to convey nuanced feelings. Inter-sentential switching constitutes 32% of the data and is typically used to mark shifts in topic, context, or level of formality, particularly when characters transition between family interactions and broader social settings. Tag switching is the least frequent type at 4%, yet it plays an important role in signaling cultural identity and social intimacy through short Mandarin or Cantonese expressions embedded in English-dominant speech. Overall, the findings indicate that code-switching in the movie functions not only as a communication strategy but also as a reflection of cultural hybridity, emotional expression, and identity negotiation among bilingual immigrants. These insights contribute to a deeper understanding of multilingual communication and may be useful for language teaching practices that emphasize sociocultural awareness.